Microengineered human blood–brain barrier platform for understanding nanoparticle transport mechanisms - Song Ih Ahn (Nature Portfolio, 2020)
Developing an in vitro blood-brain-barrier (BBB) model that reproduces the organ’s complex structure and function is an open challenge. Here the authors present a BBB-on-a-chip that includes endothelial cells, pericytes and a 3D astrocytic network which resembles the morphology and function of astrocytes in the BBB in vivo.